2019
DOI: 10.1093/intimm/dxz079
|View full text |Cite
|
Sign up to set email alerts
|

Human gain-of-function STAT1 mutation disturbs IL-17 immunity in mice

Abstract: Gain-of-function (GOF) mutations in the gene for signal transducer and activator of transcription 1 (STAT1) account for approximately one-half of patients with chronic mucocutaneous candidiasis (CMC) disease. Patients with GOF-STAT1 mutations display a broad variety of infectious and autoimmune manifestations in addition to CMC, and those with severe infections and/or autoimmunity have a poor prognosis. The establishment of safe and effective treatments based on a precise understanding of the molecular mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 86 publications
1
21
0
Order By: Relevance
“…In humans, the gain‐of‐function STAT1 mutations inhibited the development of IL‐17‐producing T cells and impaired IL‐17 immunity [45]. Introduction of the human STAT1 mutation into mice decreased the number of IL‐17‐producing cells upon Candida albicans infection [46]. Moreover, the death receptor Fas was demonstrated to promote T H 17 cell development by preventing STAT1 activation [47].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the gain‐of‐function STAT1 mutations inhibited the development of IL‐17‐producing T cells and impaired IL‐17 immunity [45]. Introduction of the human STAT1 mutation into mice decreased the number of IL‐17‐producing cells upon Candida albicans infection [46]. Moreover, the death receptor Fas was demonstrated to promote T H 17 cell development by preventing STAT1 activation [47].…”
Section: Discussionmentioning
confidence: 99%
“…In the decade since STAT1 GOF was first described, strides have been made in characterizing the disorder and its underlying pathophysiology. A prominent example is the impaired Th17 response observed in most patients, which has been linked to predisposition to fungal and bacterial infections 14 , 20 , 21 . From an autoimmune standpoint, impaired type I IFN response has been proposed as a possible contributory mechanism, given the heightened IFN signature associated with other autoimmune and inflammatory conditions 22 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Investigation on individuals that are prone to chronic mucocutaneous candidiasis (CMC) with defects in Th17 development and functionality due to single nucleotide polymorphism or as segment of syndrome have elucidated the involvement of Th17 cells in the protection of human host (5,6).The processes of Th17 cell differentiation and inborn errors of Th17 cell function in affected patients have drawn attention in recent time (7). For instance, it has been reported that mutation in some genes such as DOCK8, STAT3, STAT1, AIRE, IL-17RA, IL-17F led to impairment of Th17 development and function in humans (8).…”
Section: -Introductionmentioning
confidence: 99%
“…This is responsible for the abnormal IL-17 + T-cell development, impacting on IL-17 + T cell-mediated responses that are often antifungal in effect. The establishment of safe and effective treatments based on a precise understanding of the molecular mechanisms of this disorder is required to improve patient care(40).…”
mentioning
confidence: 99%